ANALISIS PENGARUH LAMA USAHA, USIA DAN PENDIDIKAN TERHADAP PENDAPATAN PENGELOLA UMKM KABUPATEN KULON PROGO YOGYAKARTA - Sukardi, Sukardi (Optimum: Jurnal Ekonomi dan Pembangunan, 2011)
This study aims to determine the effect of a length of business, age and education, to UMKM managers income in kabupaten of Kulonprogo. Its population is around the UMKM managers in Kulonprogo, obtained a sample of 83 respondents with a purposive sampling technique. Simultaneously, the variable length of business, age and education have a positive and significant effect on UMKM managers income in Kulonprogo. Partially, education variable is positive and significant effect on UMKM managers income in Kulonprogo.